Enhancing Students’ Listening Skill Through Dictogloss - Puspita, Nurul (Universitas Islam Negeri Raden Intan Lampung, 2016)
Dictogloss is a technique where the learner receives some spoken input, hold this in their memory for short time, and then write what they heard. Dictogloss can develop student’s listening skill, because they listen what teacher dictates in a short piece of text. The steps are students engages discussion on the topic of the upcoming text, reads the text aloud once at normal speed, reads the text again at normal, and identify similarities and differences in terms of meaning. This article refers to an action research about enhancing students’ listening skill through dictogloss at English Department IAIN Raden Intan Lampung. The steps of action research are planning, implementing, reflecting, and observing. The population of the research is the second semester students of English Department, in IAIN Raden Intan Lampung. The sample of the research consist of one class; PBI E students. The sampling technique used is purposive sampling. The instruments used to collect the data are listening test, questionnaire, observation sheet, and interview sheet. The data were analyzed by interactive model. Based on the result of the analysis, the findings of the research are: (1) Dictogloss improves the students’ listening skill ; (2) in cycle 1, that there were some of the students who could not focus on listening to the text and reconstruct it optimally; (3) in cycle 2, all of the students could focus and reconstruct the text well; (4) in cycle 1, the researcher could not emphasize the use of English and coordinated learning process; and (5) in cycle 2, the researcher used simple vocabulary and made some vocabulary games. In conclusion, that there is an improvement of the students’ listening skill after being taught using Dictogloss